ANALISIS KELENGKAPAN RESUME MEDIS DAN KETEPATAN KODING LAYANAN OPERASI KANKER PAYUDARA DI RUMAH SAKIT KANKER DHARMAIS TAHUN 2022 - Febriadi, Yudi; Nurwahyuni, Atik (UI Scholars Hub, 2024)
The background to this research is that there are still National Health Insurance (JKN) claim files being returned to the Dharmais Cancer Hospital (RSKD) with the most common causes being cases of coding confirmation and medical resumes. RSKD started using electronic medical records (eMR) in 2020. In 2018 research with a sample of 45 medical records, it was found that 2.2% of patients were incomplete in filling out the patient identity column, 91.1% of indications for admission, 44.4% of physical examinations and supporting examinations. 8.9%. In addition, it was found that 17.8% of the main diagnosis coding was inappropriate. In 2021 there were 12,941 inpatient claim files sent to BPJS Health and 179 (1.38%) files were returned due to 90% problems with medical resume completeness and coding accuracy. The aim of this research is to analyze the completeness of the contents of medical records and the accuracy of coding for inpatients for breast cancer surgery services at RSKD. This research was conducted by examining the medical resumes of breast cancer patients who underwent surgery from January to June 2022. The results of the study of 168 samples of inpatient files for breast surgery services from January to June 2022 showed that 100% of the medical record files were